Changing monetary policy rules, learning, and real exchange rate dynamics - Mark, Nelson C. 1955- (National Bureau of Economic Research, 2005)
"When central banks set nominal interest rates according to an interest rate reaction function, such as the Taylor rule, and the exchange rate is priced by uncovered interest parity, the real exchange rate is determined by expected inflation differentials and output gap differentials. In this paper I examine the implications of these Taylor-rule fundamentals for real exchange rate determination in an environment where market participants are ignorant of the numerical values of the model's coefficients but attempt to acquire that information using least-squares learning rules. I find evidence that this simple learning environment provides a plausible framework for understanding real dollar--DM exchange rate dynamics from 1976 to 2003. The least-squares learning path for the real exchange rate implied by inflation and output gap data exhibits the real depreciation of the 70s, the great appreciation (1979.4-1985.1) and the subsequent great depreciation (1985.2-1991.1) observed in the data. An emphasis on Taylor-rule fundamentals may provide a resolution to the exchange rate disconnect puzzle"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Foreign exchange -- Econometric models